STRENGTHENING TREATMENT OF DEEP-DRAWING DIES - N. A. Galynskaya; N. G. Koukhareva; S. N. Petrovich; G. V. Stassevich (Наука и техника)
The paper investigates a possibility to increase resistance of die tool for deep-drawing while applying surface strengthening with the help of diffusion carbidized coatings. Execution of diffusion carbidization in the developed powder media on the Х12Ф1 die steel has ensured obtaining of diffusion layers that have highly dispersed structure without any traces of internal oxidation.The executed investigations on studying influence of peculiar structural features of carbide layers on their mechanical properties have made it possible to determine an optimum structure and character of carbide distribution in a layer depending on the thermo-diffusion treatment modes. The results obtained with the help of the modern methods have found their practical application in development of new technologies for die and punch stamps for deep drawing of hydraulic actuator parts at the Minsk Mechanical Works named after S. I. Vavilov.